ANALISIS PENGARUH PENGETAHUAN MEREK TERHADAP MINAT BELI PADA SMARTPHONE SAMSUNG GALAXY SERIES (Studi Pada Mahasiswa Universitas Brawijaya) - Syarifah Soraya Alqadrie (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objectives of this research are to examine and analyze the simultaneous and/or partial influence of brand knowledge, which consist of brand awareness and brand image, on customers’ purchase intention toward Samsung Galaxy series smartphone and to determine the variable that has a dominant influence on purchase intention. This explanatory research explains causal relationship between dependent variable and independent variables through hypothesis testing. Using purposive sampling technique, 210 Brawijaya University students were selected as the respondents. To identify the influence of independent variables on dependent variable, this research uses multiple linear regression analysis. F test, t test, and dominant test were used to test the hypothesis. Based on the result of data advisability test, namely validity and reliability tests, the indicators of this research are stated valid and reliable the result of classical assumption test indicates that the regression model in this research is normally distributed and free of multicollinearity, and heteroscedasticity. The calculation of multiple linear regression analysis in this research can be interpreted that brand awareness and brand image simultaneously and partially have a significant influence on purchase intention. The result also shows that brand image has a dominant influence on purchase intention.keywords : Brand Knowledge, Brand Awareness, Brand Image, Purchase Intention